Effects of four novel root-end filling materials on the viability of periodontal ligament fibroblasts - Makbule Bilge Akbulut; Pembegul Uyar Arpaci; Ayce Unverdi Eldeniz (Restorative Dentistry & Endodontics, 2018)
ObjectivesThe aim of this in vitro study was to evaluate the biocompatibility of newly proposed root-end filling materials, Biodentine, Micro-Mega mineral trioxide aggregate (MM-MTA), polymethylmethacrylate (PMMA) bone cement, and Smart Dentin Replacement (SDR), in comparison with contemporary root-end filling materials, intermediate restorative material (IRM), Dyract compomer, ProRoot MTA (PMTA), and Vitrebond, using human periodontal ligament (hPDL) fibroblasts.Materials and MethodsTen discs from each material were fabricated in sterile Teflon molds and 24-hour eluates were obtained from each root-end filling material in cell culture media after 1- or 3-day setting. hPDL fibroblasts were plated at a density of 5 × 103/well, and were incubated for 24 hours with 1:1, 1:2, 1:4, and 1:8 dilutions of eluates. Cell viability was evaluated by XTT assay. Data was statistically analysed. Apoptotic/necrotic activity of PDL cells exposed to material eluates was established by flow cytometry.ResultsThe Vitrebond and IRM were significantly more cytotoxic than the other root-end filling materials (p < 0.05). Those cells exposed to the Biodentine and Dyract compomer eluates showed the highest survival rates (p < 0.05), while the PMTA, MM-MTA, SDR, and PMMA groups exhibited similar cell viabilities. Three-day samples were more cytotoxic than 1-day samples (p < 0.05). Eluates from the cements at 1:1 dilution were significantly more cytotoxic (p < 0.05). Vitrebond induced cell necrosis as indicated by flow cytometry.ConclusionsThis in vitro study demonstrated that Biodentine and Compomer were more biocompatible than the other root-end filling materials. Vitrebond eluate caused necrotic cell death.